Preparation method of starch-based porous material with high oil and water absorption characteristics

The starch shell is destroyed by low-temperature chemical gelatinization, which promotes enzyme hydrolysis and forms a porous structure, which solves the problem of low porosity of porous starch and significantly improves its adsorption characteristics and industrial application efficiency.

CN119431874APending Publication Date: 2025-02-14SICHUAN RES INST OF SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568098.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The porosity of existing porous starch is low, which affects its industrial application. The enzyme preparation efficiency of a single enzyme is low, and the pore formation is slow and time-consuming.

Method used

The starch shell is destroyed by low-temperature chemical gelatinization method, exposing the amorphous shell/growth ring structure, allowing the enzyme to quickly hydrolyze and expand the gap between branched molecular clusters, forming a pore size of multiple penetrating particles, and improving the adsorption characteristics of porous starch.

Benefits of technology

It significantly improves the oil and water absorption capacity of porous starch, simplifies the preparation process, reduces costs and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431874A_ABST
    Figure CN119431874A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a starch-based porous material with high oil and water absorption characteristics, which comprises the following steps: preparing a surface modification reagent, mixing the reagent with starch, heating at low temperature, continuously stirring for gelatinization, terminating the reaction, and repeatedly centrifuging and washing; adding water into the surface modified starch, resuspending, repeatedly breaking walls to remove surface shells, centrifuging, washing with alcohol, drying and collecting; mixing the collected starch with a mixed enzyme solution for enzymolysis; after continuous oscillation reaction, adjusting the pH value to be acidic to inactivate the enzyme, then adjusting to be neutral, centrifuging, discarding supernate, washing with water, centrifuging, drying, sieving, collecting and storing to obtain porous starch; adding a certain proportion of oil and water into the starch, oscillating, mixing, centrifuging and measuring the adsorption capacity; the adsorption capacity of the starch is effectively improved by a low-consumption, low-cost, simple and feasible method, and the stripping particle surface shell structure is provided for the first time to improve the mixed enzymolysis mode, so that the oil-water adsorption capacity of the porous material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of food technology, and in particular to a method for preparing a starch-based porous material with high oil and water absorption properties. Background Art

[0002] With the development of the food industry, the demand for modified starch production capacity and categories continues to increase. In 2022, my country's modified starch production has reached 1.9438 million tons. The price of modified starch is generally low, and its market size is only 17.441 billion yuan, a year-on-year increase of 6.56% compared with 2021. Porous starch, as a high-priced modified starch, is used in the fields of food nutrients and flavor substances due to its excellent adsorption and sustained-release properties. As one of the most important qualities of porous starch, the pore structure can give a higher specific surface area and improve the efficiency of material transport. It changes with the change of starch source and preparation method. The low porosity of porous starch has always been a technical difficulty that has plagued its industrial application, seriously affecting the industrial upgrading of modified starch.

[0003] Compared with physical and chemical techniques, the preparation of porous starch by enzyme technology is controllable and effective, and the process is more environmentally friendly. The number, size, depth, and particle stability of the pores can be adjusted by controlling the degree of hydrolysis of starch. In the enzymatic preparation of porous starch, α-amylase and saccharifying enzyme are the two most widely used enzymes. However, the effect of a single enzyme is limited, and the pore-forming effect is easily affected by the source of starch and is unstable. In order to improve the utilization efficiency of porous starch prepared by enzymatic method, composite enzyme treatment is often required, but the complex structure of starch itself makes pore formation slow and time-consuming, and the pore diameter and pore depth are insufficient. This problem greatly limits the industrialization process of porous starch. Summary of the invention

[0004] In view of the defects in the prior art, the purpose of the present invention is to provide a method for preparing a starch-based porous material with high oil and water absorption properties. The present invention is a method for effectively improving the oil and water absorption capacity of corn porous starch and potato porous starch in a low-cost and simple and easy method. The present invention destroys the dense accumulation of single or double helices of straight-chain starch and amylopectin molecules in the starch shell through the surface gelatinization of starch, exposing a relatively loose amorphous shell / growth ring structure, so that the amylase rapidly hydrolyzes and expands the gaps between the branched molecular clusters, gradually penetrates into the interior of the particles, and the internal and external hydrolysis is carried out simultaneously to form multiple pores that penetrate the particles, forming a stable and dense pore structure. At present, there is no report on improving the enzymatic hydrolysis mode, improving the enzymatic hydrolysis efficiency, and enhancing the adsorption characteristics of porous starch by destroying the shell by chemical gelatinization.

[0005] The object of the present invention is achieved through the following solutions:

[0006] The present invention provides a method for preparing a starch-based porous material with high oil and water absorption properties, comprising the following steps:

[0007] S1. Mix the surface modification reagent and starch, heat at low temperature, and continue to stir to gelatinize. After terminating the reaction, centrifuge and wash with water; resuspend in water and then break the wall to remove the gelatinized shell on the surface, centrifuge, wash with alcohol, dry, and collect;

[0008] S2, mixing the starch obtained in step S1 with the mixed enzyme solution for enzymolysis; after continuous oscillation reaction, adjusting the pH value to acidic to inactivate the enzyme and then adjusting to neutral, centrifuging, washing, centrifuging, drying, sieving, collecting and storing to obtain porous starch.

[0009] As an embodiment, in step S1, the surface modification agent is a calcium chloride aqueous solution with a concentration of 3 to 4 mol / L. The present invention adopts a low-temperature chemical gelatinization method, and only peels off or partially peels off the surface shell of starch by surface gelatinization and wall breaking, which has no effect on the internal structure of starch particles.

[0010] As an embodiment, the starch is selected from corn starch and / or potato starch. Corn starch and potato starch are one of the main raw materials in the modified starch industry, and can increase the adsorption and sustained release capacity of the prepared microporous starch.

[0011] As an embodiment, in step S1, the material-liquid ratio of starch to surface modification agent is 10 g: 75-80 mL. In some implementation examples, the material-liquid ratio is 10 g: 75 mL.

[0012] As an embodiment, step S1, the gelatinization temperature is 30-35°C, the stirring speed is 150-200r / min, and the stirring time is 3-5min. Repeat step S1 to add water to resuspend, break the wall, and centrifuge, and detach the outer shell of the starch 2-3 times until the centrifugal supernatant is clear. In some implementation examples, the gelatinization temperature is 30°C, and the stirring speed during gelatinization is 200r / min. After the gelatinization is completed, the gelatinized starch is immediately added with 6-8 times the volume of the gelatinizer and stirred to stop the gelatinization reaction. The starch suspension is centrifuged at 3000-5000r / min for 10min, and the lower starch sample is continued to be washed with distilled water, centrifuged, and cycled twice. After the starch sample is resuspended in water, it is passed through a beater with a power of 600-800W and a speed of 8000-9000r / min, and the wall is broken intermittently for 10-15min (running 1-2min, intermittent 1-2min). Centrifuge at 3000-5000r / min for 8-10min, and discard the turbid supernatant. Resuspend the starch sample in water, and repeat the cell wall breaking 2-3 times until the supernatant is clear. Centrifuge, wash with alcohol, dry (air dry), weigh, and pass through a (100 mesh) sieve to obtain the starch with the shell removed.

[0013] As an embodiment, step S1 further comprises: measuring the shelling degree of the starch obtained by alcohol washing. Further preferably, the shelling degree is 5%-11%, and more preferably, the shelling degree is 10±0.5%.

[0014] As an embodiment, in step S2, the composition of the mixed enzyme is α-amylase (EC 3.2.1.1) and saccharifying enzyme (EC 3.2.1.3) from Aspergillus oryzae, and the addition amount is: 4-5U α-amylase and 4-5U saccharifying enzyme per gram of starch. The enzymatic hydrolysis time of the mixed enzyme is 12-24 hours.

[0015] As an embodiment, in step S2, the enzymatic hydrolysis oscillation speed is 50-80 r / min, and the enzymatic hydrolysis temperature is 50-60° C. In some implementation examples, the enzymatic hydrolysis oscillation speed is 50 r / min, and the enzymatic hydrolysis temperature is 50° C.

[0016] In some implementation examples, 0.1 mol / L HCl solution is used to adjust the pH to 3.5 to inactivate the enzyme, and 15 minutes later, 0.1 mol / L NaOH solution is used to adjust the pH to neutral.

[0017] As an implementation scheme, in step S2, the centrifugal speed is 3000-5000 r / min for 8-10 min, the drying temperature is 25-40° C., the drying time is 36-48 h, and the sieve mesh is 100 mesh.

[0018] In the present invention, the wall breaking, centrifugation and water washing in step S1 can be repeated to peel off the surface gelatinized shell layer. The dipole metal interaction (complex formation) between the starch-OH groups on the surface of the starch granules and the calcium ions in the concentrated solution generates enough heat to gelatinize the peripheral starch. Stopping the reaction requires rapid cooling and dilution of the concentration by ice water. Repeated water washing and centrifugation will wash away the calcium ions attached to the surface of the starch granules, and the gelatinized layer adhering to the surface will be removed by repeated wall breaking.

[0019] As an embodiment, step S2 further comprises: adding a certain proportion of oil and water to the obtained porous starch, and vibrating and adsorbing the starch. A certain proportion of oil and water is added to the starch, vibrated and mixed, centrifuged, and the adsorption capacity is measured.

[0020] As an embodiment, the porous starch is mixed with soybean oil or distilled water at a solid-liquid ratio of 0.5-1 g:10 mL, vortexed, centrifuged and the supernatant removed, the precipitate weighed and the absorbance calculated. In some implementation examples, the vortex is oscillated for 20 min, centrifuged at 1610×g for 30 min and the supernatant removed, the precipitate weighed and the absorbance calculated.

[0021] The present invention also provides a use of a starch-based porous material with high oil and water absorption properties obtained by the above method.

[0022] As an embodiment, the use includes being used as a wall material to encapsulate hydrophobic bioactive materials and being applied in the fields of food nutrient substances, flavor substances delivery, etc.

[0023] The present invention removes the outer shell of starch by using surface modification reagents and a wall-breaking method, destroying the tight stacking of the aggregated structure in the starch outer shell, allowing the amylase to rapidly hydrolyze and expand the gaps between the branched molecular clusters, gradually penetrate into the particles, and simultaneously hydrolyze inside and outside to form multiple apertures that penetrate the particles, forming a stable and dense pore structure, and significantly improving the adsorption properties of porous starch, especially the oil absorption properties.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The method of the present invention has simple steps, is easy to implement, has high production efficiency and low operating cost;

[0026] (2) The present invention removes the outer shell of starch by using surface modification reagents and a wall-breaking method, thereby improving the enzymatic hydrolysis efficiency and the compactness and uniformity of the pore structure, and significantly improving the adsorption characteristics of porous starch. The porous starch can be used as a wall material to encapsulate hydrophobic bioactive materials and is applied to the fields of food nutrient substances and flavor substances delivery;

[0027] (3) The porous starch prepared by the present invention can also be used in industrial applications such as film, coating and gel production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0029] Figure 1 This is the adsorption capacity diagram of starch adsorbing soybean oil;

[0030] Figure 2 This is the adsorption capacity diagram of starch for distilled water;

[0031] Figure 3 This is a scanning electron microscope image of porous starch. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] The following examples and comparative examples relate to a method for determining the adsorption capacity of porous starch, specifically, starch (1.0 g) was mixed with soybean oil or deionized water (10.0 mL) at room temperature (25±1° C.), vortexed for 20 min, and then centrifuged at 1610×g for 30 min. The precipitate was weighed immediately after the supernatant was removed.

[0034] The starch absorption rate including WA (%) and OA (%) is calculated according to formula (1):

[0035]

[0036] Where W 1 (g) is the weight of the precipitate after adsorption of water or oil, W 2 (g) is the weight of dry starch.

[0037] Example 1

[0038] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties, and the steps are as follows:

[0039] Step 1: prepare a surface gelling agent, a 4 mol / L calcium chloride solution, weigh 444 g of calcium chloride and dissolve it in water, and then continue to add water to make up to 1 L after cooling to room temperature.

[0040] Step 2: Disperse 20 g corn starch (dry basis) in 150 mL 4 M CaCl 2 The solution was stirred magnetically at 200 r / min at a temperature of 30°C and a reaction time of 5 min.

[0041] Step 3: After the reaction is completed, add 1200 mL of ice water (0°C) to stop the gelatinization process. Centrifuge the gelatinized solution at 3000 r / min for 10 min. Remove the supernatant and wash twice with 2 L of distilled water to remove residual CaCl 2 .

[0042] Step 4: Resuspend the sample in 300 mL of distilled water and pass it through a pulper at 800 W and 9000 r / min for 15 min (1 min of operation and 1 min of rest). Then, centrifuge the mixture at 3000 r / min for 10 min and collect the precipitate. Repeat this process until the supernatant is transparent and colorless.

[0043] Step 5: The obtained starch granules were washed twice with anhydrous ethanol and dried in an oven at 40° C. for 48 h. The degree of dehulling of starch was calculated according to the following formula: degree of dehulling=(1-mass of remaining granules / mass of original starch)×100%.

[0044] Step 6. Suspend the starch (5.0 g) obtained in step 5 in 25 mL of 20 mM PBS at pH 6.0, and add 25 U of α-amylase and 20 U of saccharifying enzyme. The sample was shaken at 80 r / min in a shaking water bath (50 r / min) at 50 ° C for 12 hours. After the reaction, the pH was adjusted to 3.5 with 0.1 mol / L HCl solution to inactivate the enzyme, and after 15 minutes, the pH was adjusted to neutral with 0.1 mol / L NaOH solution. Wash with water, centrifuge and dry (centrifuge at 4000 r / min for 10 minutes, dry at 40 ° C), and sieve to obtain porous starch.

[0045] Step 7: Mix starch (1.0 g) with soybean oil or deionized water (10.0 mL) at room temperature (25 ± 1 °C), vortex for 20 min, and then centrifuge at 1610 × g for 30 min. After removing the supernatant, weigh the precipitate immediately. The starch absorption rate includes WA (%) and OA (%) and is calculated as follows:

[0046] Where W 1 (g) is the weight of the precipitate after adsorption of water or oil, W 2 (g) is the weight of dry starch.

[0047] Implementation effect: the dehulling degree of corn starch is 10.3%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 86.9%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this embodiment is 116.9%. Figure 3 It can be seen that the porous starch prepared in Example 1 has deep and numerous pores.

[0048] Example 2

[0049] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0050] In step 2, the gelatinization heating and stirring time is 3 minutes.

[0051] Implementation effect: The dehulling degree of corn starch is 5.2%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 72.1%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2It can be seen that the water absorption capacity of the porous starch prepared in this embodiment is 103.8%. Comparative Example 1 shows that when the surface gelatinization degree is reduced, the starch enzymatic hydrolysis effect decreases, and the adsorption capacity decreases accordingly. This may be because the smaller gelatinization degree has limited damage to the shell layer and the lifting effect is poor. Considering that the surface gelatinization causes some loss of starch raw materials, in the case of a lower shelling degree, it is preferred that the shelling degree of 10% is used to prepare porous starch.

[0052] Example 3

[0053] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0054] Skip steps 1, 2, 3, 4 and 5 and go directly to step 6.

[0055] Implementation effect: Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 65.3%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this embodiment is 82.5%. It can be seen that the surface gelatinization treatment has a significant effect on improving the adsorption capacity of porous starch. Figure 3 It can be seen that the pores of the porous starch prepared in Example 3 do not penetrate the interior of the particles, but are surface pits, resulting in its adsorption capacity being lower than that of Example 1, indicating that the present invention destroys the starch gelatinization shell through the surface gelatinization and wall breaking method of starch, so that the amylase can quickly hydrolyze and expand the gaps between the branched molecular clusters, gradually penetrate into the interior of the particles, and the internal and external hydrolysis are carried out simultaneously to form multiple pores that penetrate the particles, forming a stable and dense pore structure.

[0056] Example 4

[0057] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0058] The enzymatic hydrolysis time in step 6 is 36 hours.

[0059] Implementation effect: the dehulling degree of corn starch is 10.3%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 63.0%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2It can be seen that the water absorption capacity of the porous starch prepared in this example is 85.2%. The adsorption capacity of the porous starch is lower than that of Example 3, indicating that too long enzymatic hydrolysis time will reduce the adsorption capacity of the porous starch, which may be because too long enzymatic hydrolysis time causes the pores to be too large, reducing the embedding capacity.

[0060] Example 5

[0061] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0062] Do not proceed to step 1 and replace the CaCl 2 The solution was replaced with water.

[0063] Implementation effect: the dehulling degree of corn starch is 0%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 64.5%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this embodiment is 86.2%. The oil absorption and water absorption capacity of the porous starch prepared in Example 5 are lower than those in Example 1, indicating that CaCl 2 As a surface modifier, adding water alone cannot gelatinize the surface layer of starch, so that breaking the starch wall cannot remove the surface layer of starch. The starch maintains its original structure. The adsorption capacity of the porous starch after enzymatic hydrolysis is close to that of the porous starch only enzymatically hydrolyzed in Example 3.

[0064] Example 6

[0065] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0066] Do not proceed to step 4.

[0067] Implementation effect: the dehulling degree of corn starch is 10.3%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 63.2%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this example is 79.5%. The oil absorption and water absorption capacity of the porous starch prepared in Example 6 are lower than those in Example 1, indicating that the starch only undergoes gelatinization of the surface shell layer, and the surface shell layer is not removed by breaking the wall, which cannot improve the adsorption capacity of the porous starch.

[0068] Example 7

[0069] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0070] In step 6, only 50 U of α-amylase was added, without saccharifying enzyme.

[0071] Implementation effect: the dehulling degree of corn starch is 10.3%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 60.5%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this example is 80.9%. The oil and water absorption capacity of the porous starch prepared in Example 6 is lower than that of Example 1, indicating that the adsorption capacity of the porous starch prepared by using α-amylase alone is lower than that of the porous starch prepared by the composite enzyme.

[0072] Example 8

[0073] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0074] In step 6, only 50 U of saccharifying enzyme was added, without α-amylase.

[0075] Implementation effect: The gelatinization degree of corn starch is 10.3%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 58.6%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this example is 75.6%. The oil and water absorption capacity of the porous starch prepared in Example 6 is lower than that of Example 1, indicating that the adsorption capacity of the porous starch prepared by using α-amylase alone is lower than that of the porous starch prepared by the composite enzyme.

[0076] Example 9

[0077] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0078] In step 2, replace corn starch with potato starch.

[0079] Implementation effect: the dehulling degree of potato starch is 10.0%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 47.2%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this embodiment is 74.1%. Potato starch particles are relatively large and difficult to be enzymatically hydrolyzed, and the adsorption capacity of its porous starch is not as good as that of corn porous starch. Figure 3 It can be seen that the pores of potato porous starch are mainly formed in the relatively loose interior, and the rest of the position is relatively smooth. The number of pores is lower than that of corn porous starch, so its adsorption capacity is not as good as that of corn porous starch. Figure 3 This indicates that surface gelatinization of starch can destroy the dense accumulation of single or double helices of straight-chain starch and amylopectin molecules in the starch shell, exposing a loose amorphous shell / growth ring structure, allowing amylase to rapidly hydrolyze and expand the gaps between branched molecular clusters, gradually penetrating into the interior of the particles. Internal and external hydrolysis proceed simultaneously to form more pores, which can increase the adsorption capacity of porous starch.

[0080] Example 10

[0081] This embodiment relates to a method for preparing a starch-based porous material with high oil and water absorption properties. The method is the same as that in Embodiment 1, except that:

[0082] In step 2, corn starch is replaced with potato starch. Step 1, step 2, step 3, step 4 and step 5 are omitted, and step 6 is directly performed.

[0083] Implementation effect: The dehulling degree of potato starch is 0%. Figure 1 The adsorption capacity of starch to soybean oil is shown in Figure 2. Figure 1 It can be seen that the oil absorption capacity of the porous starch prepared in this embodiment is 32.8%; Figure 2 This is a comparison chart of the adsorption capacity of starch to distilled water. Figure 2 It can be seen that the water absorption capacity of the porous starch prepared in this example is 55.2%. The adsorption capacity of the porous starch in Example 10 is lower than that in Example 9, indicating that gelatinization and removal of the surface shell of potato starch can increase the adsorption capacity of the porous starch.

[0084] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.

Claims

1. A method for preparing a starch-based porous material with high oil and water absorption properties, characterized in that: The following steps are involved: S1. Mix the surface modification reagent and starch, heat at low temperature, and continue to stir to gelatinize. After terminating the reaction, centrifuge and wash with water; resuspend in water and then break the wall to remove the gelatinized shell on the surface, centrifuge, wash with alcohol, dry, and collect; S2, mixing the starch obtained in step S1 with the mixed enzyme solution for enzymolysis; after continuous oscillation reaction, adjusting the pH value to acidic to inactivate the enzyme and then adjusting to neutral, centrifuging, washing, centrifuging, drying, sieving, collecting and storing to obtain porous starch.

2. The preparation method according to claim 1, characterized in that: In step S1, the starch raw material is corn starch and / or potato starch, and the surface modification agent is a calcium chloride aqueous solution with a concentration of 3 to 4 mol / L.

3. The preparation method according to claim 1, characterized in that: In step S1, the material-liquid ratio of starch to surface modification agent is 10 g:75-80 mL; the gelatinization temperature is 30-35° C., the stirring speed is 150-200 r / min, and the stirring time is 3-5 min.

4. The preparation method according to claim 1, characterized in that: In step S1, the pulping machine is used for pulping, with a power of 600-800 W, a rotation speed of 8000-9000 r / min, and intermittent pulping for 10-15 min.

5. The preparation method according to claim 1, characterized in that: In step S2, the enzymatic hydrolysis time of the mixed enzyme is 12 to 24 hours, the enzymatic hydrolysis oscillation speed is 50 to 80 r / min, and the enzymatic hydrolysis temperature is 50 to 60°C.

6. The preparation method according to claim 1, characterized in that: Repeat step S1, resuspending with water, breaking the starch wall, and centrifuging to separate the starch outer shell layer 2 to 3 times.

7. The preparation method according to claim 1, characterized in that: Step S1 also includes: measuring the degree of dehulling of the starch obtained by alcohol washing.

8. The preparation method according to claim 1, characterized in that: Step S2 also includes: adding a certain proportion of oil and water to the obtained porous starch, and performing oscillation adsorption.

9. The preparation method according to claim 8, characterized in that: In step S2, the porous starch is mixed with soybean oil or distilled water at a solid-liquid ratio of 0.5-1 g:10 mL, vortexed, centrifuged and the supernatant is removed, the precipitate is weighed and the absorbance is calculated.

10. Use of a starch-based porous material obtained by the method according to any one of claims 1 to 9, characterized in that: The uses include being used as a wall material to encapsulate hydrophobic bioactive materials and being applied in the field of transporting food nutrients and flavor substances.